Tandziful ‘Am: Islamic Boarding School Traditions in Caring for Harmony Interreligious People - Qodim, Husnul; Karim, Abdul; Maulani, Maulani; Qaaf, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This article discusses the tradition of fanciful 'being carried out by the Darul Hikmah Islamic boarding school in maintaining harmony between Muslims and Christians in the city of Medan. This study uses a qualitative method with a field research type. The subjects of this study were teachers, students, and the Christian community living around the Darul Hikmah Islamic boarding school in Medan. The object of this study is the tradition of fanciful 'being carried out by the Darul Hikmah Islamic boarding school and the surrounding community to clean the environment around the Islamic boarding school and strengthen the bonds of brotherhood between religious communities. This study found that the tradition of fanciful 'being carried out by the Darul Hikmah Islamic boarding school has a major impact on the harmony of Muslims and Christians in the city of Medan, especially in the community around the Islamic boarding school, as evidenced by the absence of disputes between the Muslim community living in the Islamic boarding school and the Christian community living in the area around the Islamic boarding school, even good interaction is established between the two as evidenced by the attitude of the Christian community who are always willing to cooperate in various social activities, and the existence of Islamic boarding school policies in the use of loudspeakers that pay attention to the comfort of the Christian community. This research has implications for revealing Islamic boarding schools' role in promoting tolerance values and providing deeper insights into local practices contributing to social cohesion in multi-religious societies.